2022
DOI: 10.18203/2394-6040.ijcmph20222379
|View full text |Cite
|
Sign up to set email alerts
|

Common chronic conditions in pediatric primary care

Abstract: Chronic health conditions comprise illnesses as well as physical disabilities that last longer than 12 months and limit the patient’s usual activity. The prevalence of chronic illnesses and disabilities in children and adolescents has more than doubled in the last 60 to 70 years. Common chronic conditions encountered among children across the globe include bronchial asthma, cystic fibrosis, diabetes mellitus, epilepsy, and developmental disabilities like cerebral palsy, in addition to congenital and heredofami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…29 30 The common diagnoses in our study, such as cancer, seizure disorders and endocrine disorders, align with global trends. 31 We found the highest burden among caregivers of children with congenital cardiac diseases, followed by CP and musculoskeletal disorders. Piran et al reported the highest caregiver burden in CP, attributing it to the wide array of challenges posed by the condition, encompassing motor, mental, emotional and communication impairments, which not only intensify caregiving demands but also strain finances and disrupt family routines.…”
Section: Discussionmentioning
confidence: 75%
“…29 30 The common diagnoses in our study, such as cancer, seizure disorders and endocrine disorders, align with global trends. 31 We found the highest burden among caregivers of children with congenital cardiac diseases, followed by CP and musculoskeletal disorders. Piran et al reported the highest caregiver burden in CP, attributing it to the wide array of challenges posed by the condition, encompassing motor, mental, emotional and communication impairments, which not only intensify caregiving demands but also strain finances and disrupt family routines.…”
Section: Discussionmentioning
confidence: 75%